Hubungan Antara Ruang Lingkup Evaluasi Pembelajaran PAI dengan Pembentukan Karakter Siswa di SD Negeri Ngebel Kasihan Bantul - Ahmad Hilmy Mochayar; Wahyu Kholis Prihantoro; M. Abdul Fattah; Aisyah Luthfiana; Nur Arfizza Ilyana; Riska Five Cahyaningsih; Nashrullah Zaki (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Evaluation of Islamic Religious Education (PAI) learning plays a strategic role in assessing the achievement of educational goals while supporting the character development of students. The evaluation process not only considers cognitive aspects but also includes affective and psychomotor aspects, such as the appreciation of religious values, noble morals, and the ability to perform religious services. This study aims to describe the relationship between the scope of PAI evaluation and the process of character development of students. The method used is a descriptive qualitative approach, with the research location at SDN Ngebel, Kasihan, Bantul. The research subjects included PAI teachers, students in grades I, V, and VI, and several parents. Data were collected through interviews with teachers, students, and guardians, observations of learning activities and religious practices, and documentation, including records of grades and religious activity agendas. Using the Miles and Huberman interactive model, data analysis included the stages of presentation, reduction, and drawing conclusions. Triangulation methods and sources ensured the validity of the data. The results showed that the implementation of a comprehensive PAI evaluation, which included academic assessment, religious practices, and moral behavior, had a significant impact on the development of student character. This is especially true in terms of religiosity, discipline, and responsibility. Therefore, the broader and more integrated the scope of Islamic Religious Education (PAI) evaluation, the greater its contribution to the overall character formation of students.